2022
DOI: 10.1371/journal.pone.0271197
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatitis C virus infection status and genotype with kidney disease risk: A population-based cross-sectional study

Abstract: Background Whether there is difference in kidney disease risk between chronic hepatitis C virus (HCV) infection and resolved HCV infection remains inconclusive. Additionally, the impact of different HCV genotypes on kidney disease risk is relatively unknown. Accordingly, we conducted a population-based cross-sectional study to investigate the association of HCV infection status and genotype on kidney disease risk. Methods The study population were adult participants of 1999–2018 National Health and Nutrition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Therefore, we could not assess the relationship between detectable HCV RNA and UACR or ABI in patients with HCV Ab seropositivity. The risk of kidney disease, defined as a UACR ≥ 30 mg/g or an eGFR < 60 mL/min/1.73 m 2 , has been reported to not be significantly different between resolved HCV infection (undetectable HCV RNA) and chronic HCV infection (detectable HCV RNA) in the patients with HCV Ab seropositivity; however, the risk of kidney disease might be higher in patients with HCV genotype 1 than in those with other HCV genotypes 52 . Fourth, we only included patients enrolled in the P4P program, which has been reported to attenuate chronic diabetic complications 53 55 .…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we could not assess the relationship between detectable HCV RNA and UACR or ABI in patients with HCV Ab seropositivity. The risk of kidney disease, defined as a UACR ≥ 30 mg/g or an eGFR < 60 mL/min/1.73 m 2 , has been reported to not be significantly different between resolved HCV infection (undetectable HCV RNA) and chronic HCV infection (detectable HCV RNA) in the patients with HCV Ab seropositivity; however, the risk of kidney disease might be higher in patients with HCV genotype 1 than in those with other HCV genotypes 52 . Fourth, we only included patients enrolled in the P4P program, which has been reported to attenuate chronic diabetic complications 53 55 .…”
Section: Discussionmentioning
confidence: 98%
“…Prevalent eGFR < 60 mL/min/1.73 m 2 or urinary albumin/creatinine ratio ≥ 30 mg/g was defined as kidney disease in this study. They concluded that genotype 1, in both resolved and chronic HCV infections, was associated with higher risk of kidney disease [ 28 ]. In our study, the results show that genotype 2 may have greater risk of albuminuria, instead of focusing on eGFR decline in patients with an HCV infection.…”
Section: Discussionmentioning
confidence: 99%